Neglected tropical diseases vectors occurrence data identified during medical consultations in hospitals in southern and central Benin - Gbenou, Tania, Sandrine; Koura, Kourouma; Kakpo, Sunday, Berlioz; Apélété, Eben-ezer; Kotin, Justine; Aïkpon, Gorgias; Ganglo, Cossi, Jean (My University, 2023)
Neglected tropical diseases are a group of preventable and curable diseases that affect 1.5 billion people, 40% of whom live in Africa. These diseases affect the poorest and most vulnerable populations living in remote areas of Africa. They disfigure and disable, prevent children from attending school and parents from working limiting their potential and leaving people trapped in poverty. The occurrences described in this publication cover Benin from January 2, 2015 to December 30, 2020. Patient registration records were used to extract occurrence data. A total of 7306 occurrences of neglected tropical disease vectors belonging to 7 species, 7 families and 5 orders were recorded. All occurrences have geographical coordinates. The large volume of data collected, the wide geographic coverage, and the long-term nature of the observations determined the value of their inclusion in the GBIF site and the need to publish them.
Keywords: borne; disease; tropical; vector